Growth, yield and fruit quality of 'maçã' banana under different rates of phosphorus fertilization - Batista Bolfarini, Ana Carolina [UNESP]; Leonel, Sarita [UNESP]; Leonel, Magali [UNESP]; Tecchio, Marco Antonio [UNESP]; de Souza Silva, Marcelo [UNESP]; Azevedo Souza, Jackson Mirellys [UNESP] (Southern Cross Publishing, 2016)
The aim of this study was to evaluate the agronomic performance and fruit quality of 'Maçã' banana cultivar. A field experiment was conducted to study the effect of phosphorus (P) on the cultivar. The study area presents a subtropical climate, where the mean temperature is 22°C; and the mean rainfall is 1377 mm. The experiment was conducted from November 2012 to May 2014. The experiment design was totally randomized, consisting of six treatments (0, 40, 60, 80, 100 and 120 kg P2O5 ha-1) and seven repetitions. The results indicated that plant height, pseudo-stem diameter, number of live leaves, yield and fruit numbers per bunch increased at 51, 45, 44, 34 and 40 kg P2O5 ha-1, respectively. The shortest harvest cycle was of 480 days at 60 kg P2O5 ha-1. In unripe bananas, RSC improved 13% at 47 kg P2O5 ha-1; while the highest level of P, Ca and Mg were obtained at 74, 41 and 58 kg P2O5 ha-1, respectively. During banana ripening, maximum fruit firmness (3.07 N) was achieved at 63 kg P2O5 ha-1. Application of triple superphosphate fertilizer (at 34 kg P2O5 ha-1) increased yield, without changing physicochemical characteristics.
Keywords: Agronomic performance; Mineral nutrition; Musa; Physicochemical characteristics; Triple superphosphate